Variable opacity (Opa) outer membrane proteins account for the cell tropisms displayed by Neisseria gonorrhoeae for human leukocytes and epithelial cells - Kupsch, E.M.; Knepper, B.; Kuroki, T.; Heuer, I.; Meyer, T.F. (The EMBO journal, 1993)
Opacity proteins (Opa) of Neisseria gonorrhoeae, a family of variant outer membrane proteins implicated in pathogenesis, are subject to phase variation. In strain MS11, 11 different opa gene alleles have been identified, the expression of which can be turned on and off independently. Using a reverse genetic approach, we demonstrate that a single Opa protein variant of strain MS11, Opa50, enables gonococci to invade epithelial cells. The remaining variant Opa proteins show no, or very little, specificity for epithelial cells but instead confer interaction with human polymorphonuclear neutrophils (PMNs). Thus, depending on the opa allele expressed, gonococci are capable of invading epithelial cells or of interacting with human leukocytes. The respective properties of Opa proteins are maintained independent of the gonococcal strain; thus, the specificity for epithelial cells or leukocytes is intrinsic to Opa proteins. Significant homology exists in the surface exposed variable regions of two invasion supporting Opa proteins from independent strains. Efficient epithelial cell invasion is favoured by high level Opa production, however, a 10‐fold reduction still allows significant invasion by gonococci. In contrast, recombinant Escherichia coli expressing Opa proteins adhered or invaded poorly under similar experimental conditions, thus indicating that additional factors besides Opa are required in the Opa‐mediated interaction with human cells.